COVID-19 Pandemic Adversely Affects the Provision of Desired Newborn Circumcision: Perinatal Physician Perspectives - Corona, Lauren E.; Rosoklija, Ilina; Walton, Ryan F.; Matoka, Derek J.; Seager, Catherine M.; Holl, Jane L.; Johnson, Emilie K. (Frontiers in Health Services, 2022)
Over half of boys in the United States undergo circumcision, which has its greatest health benefits and lowest risks when performed during the newborn period under local anesthesia. The COVID-19 pandemic has affected delivery of patient care in many ways and likely also influenced the provision of newborn circumcisions. Prior to the pandemic, we planned to conduct a qualitative study to ascertain physician perspectives on providing newborn circumcision care. The interviews incidentally coincided with the onset of the pandemic and thus, pandemic-related changes emerged as a theme. We elected to analyze this theme in greater detail. Semi-structured interviews were conducted with perinatal physicians in a large urban city from 4/2020-7/2020. Physicians that perform or counsel regarding newborn circumcision and physicians with knowledge of or responsibility for hospital policies were eligible. Interviews were transcribed verbatim and qualitative coding was performed. Twenty-three physicians from 11 local hospitals participated. Despite no specific COVID-19 related questions in the interview guide, nearly half of physicians identified that the pandemic affected delivery of newborn circumcision care with 8 pandemic-related sub-themes. The commonest sub-themes included COVID-19 related changes in: 1) workflow processes 2) staffing and availability of circumcision proceduralists, and 3) procedural settings. In summary, this qualitative study revealed unanticipated COVID-19 pandemic-related changes with primarily adverse effects on the provision of desired newborn circumcisions. Some of these changes may become permanent resulting in broad implications for policy makers that will likely need to adapt and redesign the processes and systems for the delivery of newborn circumcision care.